Coping style in college students - Salman, Sara Hassan; Al-Ali, Majida Hillel (Al-Adab Journal, 2021)
The research aimed to identify (coping style) the research sample consists of (400) male and female students from AL-Mustansiriyah University from both specialization (scientific and humanistic) for the academic year (2019 - 2020) and about (177) students from scientific specialize and (223) from humanistic students and about (202) from male and (198) from female. And the research used (Al-Aajam 2017) scale adopted according to Lazarus theory, which consists of (23) position for (Measuring coping styles) and it’s a Situational scale and each situation contain three Alternatives (addressing , assistance request and avoidance) , The alternatives to the answer are (3) alternatives, as the choice is based on the priority of use of the university student and the score of response where the score (1) for the third answer and the score (2) for the second answer and the score (3) for the first answer and thus the maximum score for each method in the scale (69) and the minimum score (23) with a hypothetical mean (46) score. And the research results achieved the mostly used Style among university students is primarily in the Coping manner specifically in addressing different life situations and events followed by technique of assistance request and finally the form of avoidance Style.